Pattern of sudden death at Ladoke Akintola University of Technology Teaching Hospital, Osogbo, South West Nigeria - Akinwusi PO; Komolafe AO; Olayemi OO; Adeomi AA (Vascular Health and Risk Management, 2013)
Patience Olayinka Akinwusi,1,2 Akinwumi Oluwole Komolafe,3 Olanrewaju Olayinka Olayemi,2 Adeleye Abiodun Adeomi41Department of Medicine, College of Health Sciences, Osun State University, 2Department of Medicine, LAUTECH Teaching Hospital, Osogbo, 3Department of Morbid Anatomy, Obafemi Awolowo University Teaching, Hospitals Complex, Ile-Ife, Osun State, 4Department of Community Medicine, LAUTECH Teaching Hospital, Ogbomoso, Oyo State, NigeriaBackground: The purpose of this study was to determine the etiology and epidemiologic characteristics of sudden death at Ladoke Akintola University of Technology (LAUTECH) Teaching Hospital, South West Nigeria.Methods: This was a retrospective descriptive study of all cases of natural unexpected death, either occurring out of hospital or less than 24 hours after admission to LAUTECH Teaching Hospital, over a nine-year period from January 2003 to December 2011. Data were generated from information in the case notes and autopsy reports for these cases.Results: Sudden death accounted for 29 (4.0%) of 718 adult medical deaths and 1.0% of all adult medical admissions. Out-of-hospital deaths occurred in 72.4% of cases. The mean age of the patients was 46.8 ± 11.5 (range 25–74) years. The male to female ratio was 6.25:1. Cardiovascular disease were the most common cause of death (51.7%), followed by respiratory disease (20.7%), pulmonary thromboembolism (10.4%), central nervous system disease (13.8%), gastrointestinal disorders (13.8%), severe chemical/drug poisoning (13.8%), and combined cardiovascular and central nervous system disease (13.8%). Hypertension-related causes were responsible for 14/29 (48.3%) of the sudden deaths. Hypertensive heart disease accounted for 86.7% of the cardiovascular deaths, hypertensive heart failure accounted for 73.3%, whilst all heart failure cases accounted for 80.0%. Left ventricular hypertrophy was present in 69.2% of the patients with hypertensive heart disease. Moderate to severe atheromatous changes occurred in the aorta in 38.5% of patients aged ≥50 years. No case of myocardial infarction was found.Conclusion: Hypertensive heart disease and hypertension-related disorders are the most common causes of sudden death in South West Nigeria, so effective public health strategies should be channeled towards prevention, detection, and treatment of hypertension.Keywords: sudden cardiac death, hypertensive heart disease, hypertensive heart failure, left ventricular hypertrophy, atheromatous changes